Acordo de não persecução penal: uma análise para a eficiência da atuação do Ministério Público e do instituto - Horvath, Antonio Carlos (2024)
Non-criminal prosecution agreement: an analysis of the efficiency of the actions of the Public Prosecutor's Office and the institute is the theme chosen for the development of this work. The theme is justified in the face of a post-modern social time, in which a crisis in the justice system emerges and, as a consequence, the adoption of the concept of Total Penal Science to resolve it. Based on a guiding criminal policy, focused on the consequences of the Criminal Process, utilitarian elements are used, which promotes Consensual Criminal Justice and its bargaining instruments. The recent establishment of the non-criminal prosecution agreement, a result of this era, appears to highlight the role of the Public Prosecutor's Office as a protagonist in the procedural legal business. However, it is reflected whether the accusatory body has fulfilled the constitutional scope conceived by the constituent and now outlined by the legislator of this century when regulating the non-criminal prosecution agreement, that is, whether Parquet has developed its own and uniform criminal policy focused on business. pre-procedural legal procedures, guided by efficiency. The objective of the work is to analyze whether the lack of a uniform criminal policy to deal with the non-criminal prosecution agreement harms the resolutive action of the body and, consequently, of the institute. From this analysis, it is recognized the need for the Public Prosecutor's Office to formulate its own criminal policy capable of uniform treatment of non-criminal prosecution agreements, in order to achieve the efficiency of its action and, consequently, of the non-criminal prosecution agreement. Through a dialectical exercise, descriptive analytical methods and bibliographic research are used. The study is divided into four parts, initially examining time and Law, post-modernity, the crisis of the justice system and Total Penal Science and then moving on to the study of Criminal Policy and utilitarian instruments, without forgetting the consensual means of resolving the criminal conflict and the alien experience in dealing with the issue, to, finally, analyze the institution of the non-criminal prosecution agreement, in its legal conformation, with a focus on the efficiency of the legal transaction procedural and ministerial activities. There is a need for regulatory standardization and action conveyed in the Public Prosecutor's Office's own criminal policy in order to achieve a process of results through efficient means. As well as the non[1]criminal prosecution agreement as a suitable means for resolving the criminal conflict